Improving Quality of Arabic Dates by low Doses of Irradiation - Farag Serag (Journal of Oasis Agriculture and Sustainable Development, 2021)
This work  aim to select the optimum dose of γ-rays for  keeping  quality of semi dry  dates(SDD) through studying physical, chemical ,microbiological characters besides disinfestations of dates. Three Arabic SDD varieties as Siwi (Egypt), Sukkary (Saudi Arabia) and Zahidi (Iraq) at ‘Tamar’ stage were  irradiated with γ-rays (0.0,1.0, 3.0  5.0 kGy).The storage of  packaged treated samples was extended eight months at room temperature (20 ~25 C°, 70~75%RH). The free radicals was monitored by Electron Spin Resonance (ESR), survey insects and microbes. Besides, tracking the changes of bioactive content (amino acid- AA, sugars and Soluble Solid Contents -SSC). Results revealed that ESR-signals of   edible parts were completely disappeared after one month whereas it’s present in kernels. Also, irradiation eliminated completely all stages of insects and reduced the microbial load either fungi or bacteria. HPLC- analysis of AA showed presence of seventeen one (µg/g dry weight), in all tested samples, the difference occurred due to variety and irradiation dose. Sugars were accumulated at end of   storage (8 months), whereas negligible changes were recorded in total, reducing or non-reducing sugars but were significantly between varieties. Same trends were noticed in SSC. At the end, the preferability  of using low dose  of γ–irradiation are suitable on large scale, safe alternative for using pesticides and sufficient for  keeping quality of tested  Arabic  semi dry dates without high losses in nutritive values.